Identification of the novel HLA‐B*52:01:27 allele by polymerase chain reaction sequence‐based typing. (27th February 2017) - Han, Z.‐D.; Dong, L.‐N.; Wang, W.; He, J.; Zhu, F.‐M.
Abstract : HLA‐B*52:01:27 differs from HLA‐B*52:01:01 by a single nucleotide substitution at position 681 C>T.